Pengaruh Kompetensi Terhadap Produktivitas Kerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Pemediasi - Suherman, Eman; Syafei, M Yani; Narimawati, Umi (Jurnal Agregasi, 2024)
Abstract The success of an organization in increasing employee work productivity will greatly support their ability to compete at work to be more productive so that goals can be achieved. The aim of this research is to explain the role of organizational culture in the influence of competence on work productivity. The population in this research is employees of Perumdam Tirta Bhakti, Majalengka Regency, totaling 45 employees. Sampling used a census/saturated sampling technique where the entire research population was used as the sample. The analysis method used is using SEM-PLS with the help of SmartPLS 3. The results of this research show that competency does not have a significant effect on employee work productivity, but it does have an effect on organizational culture. The main finding in this research is that organizational culture plays a full mediating role in the influence of competence on employee work productivity, meaning that competence has a positive and significant effect on employee work productivity through organizational culture. Keywords: Organizational Culture, Competence, Employee Work Productivity.